PENGARUH KARAKTERISTIK DEWAN DIREKSI TERHADAP KINERJA KEBERLANJUTAN - Regina, Sharleen; Agustina, Lidya (Unversitas Prof. Dr. Moestopo (Beragama), 2025)
This study seeks to analyze the impact between board characteristics on the sustainability performance of companies listed on the Indonesia Stock Exchange (IDX) in 2022-2023. The concept of sustainability performance focuses not only on economic goals, but includes social and environmental perspectives, where the board of directors has an important role in formulating better policies. The characteristics of the board of directors in this study include gender diversity, board size, board independence, board experience, and board tenure. This study applies a quantitative approach, this study analyzes secondary data from annual reports and sustainability reports from 142 companies that have ESG values on the IDX, which were selected through the purposive sampling method. Sustainability performance was measured using the total ESG score from the Refinitiv Platform while data analysis was conducted using multiple regression. The findings indicate that board size has a positive and significant influence on sustainability performance. In contrast, board experience has a negative effect on sustainability performance. Meanwhile, the variables of gender diversity, board independence, and board tenure show no influence on sustainability performance. The overall regression model is significant, but is only able to explain 30% of the variation in sustainability performance. The result suggests that several other factors beyond the variables examined in this study also influence sustainability performance.Keywords: Gender Diversity, Board Size, Board Experience, Board Tenure, ESG